Analysis the Role of Profitability in Moderating the Effect of Capital Structure, Investment Decisions, Liquidity and Firm Size on Firm Value - Kharisma, Billy Widoera; Tubastuvi, Naelati; Wahyuni, Sri; Fakhruddin, Iwan (Universitas Muhammadiyah Sorong, 2025)
This study aims to determine the impact of capital structure, investment decisions, liquidity, and firm size on firm value with profitability as a moderating variable. This study uses quantitative methods with secondary data from companies listed on the Indonesia Stock Exchange. The population in this study is infrastructure companies listed on the Indonesia Stock Exchange from 2021 to 2024. The sample was determined using a purposive sampling technique with a total of 112 observations. This study uses panel data regression analysis with the STATA 17 application. The result of data processing states that capital structure influences firm value. Investment decisions, liquidity, and company size cannot influence the value of the company in the infrastructure sector. Profitability is able to moderate the effect of capital structure and investment decisions on firm value. Still, it is unable to moderate the effect of liquidity and firm size on firm value. This study proves that to increase firm value, management must be able to manage capital and increase company profits to attract investors.